Effect of weakly coordinating anions on photo-stability enhancement of basic dyes in organic solvents. (January 2019) - Woo, Sung Wun; Kim, Jeong Yun; Hwang, Tae Gyu; Lee, Jae Moon; Kim, Hong Mo; Namgoong, JinWoong; Yuk, Sim Bum; Kim, Jae Pil
Abstract: Weakly coordinating anions (WCAs) offer two succinct advantages when they are introduced as counter anions in a dye. First, replacing strong electrostatic attraction between a cationic dye and its counter anion with the relatively weak electrostatic attraction from a WCA can improve photo-stability of the dye due to charge distribution. Second, the steric hindrance due to the WCAs forms a spatial obstacle between the unstable charged site of the cationic dye and an external element that may degrade the dye. In this study, WCAs are introduced as counter anions in basic dyes to improve their photostability. Basic Yellow 1, Rhodamine 6G, and Rhodamine B were selected as dyes due to their particularly low photostabilities among cationic dyes. Three WCAs were investigated, where two were composed of anions surrounded by fluorine moieties (hexafluorophosphate and bis(trifluoromethane)sulfonimide), and one is surrounded by oxygen moieties (bis(oxalate)borate) Upon dissolving these dyes in three different organic solvents (Chloroform, Methylene Chloride, and Dimethylformamide), the photostabilities of almost all the WCA-substituted dyes were comparatively improved. The photo-stability of each WCA-substituted dye was especially improved in low polarity solvents and the bis(trifluoromethane)sulfonamide-basic dye pairs showed the highest photo-stabilities among four anion-dye pairs including the unsubstituted dyes. Graphical abstract: Image 1 Highlights: Three Weakly Coordinating Anions were introduced to three basic dyes. Spectral properties and electrical conductivities of dye solutions were measured. The photo-stability of each WCA-substituted dye was especially improved in low polarity solvents. Anion with large size and fluoride-terminal groups significantly improved the photo-stability of basic dyes.